1260=30(3x+30)

Simple and best practice solution for 1260=30(3x+30) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1260=30(3x+30) equation:


Simplifying
1260 = 30(3x + 30)

Reorder the terms:
1260 = 30(30 + 3x)
1260 = (30 * 30 + 3x * 30)
1260 = (900 + 90x)

Solving
1260 = 900 + 90x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-90x' to each side of the equation.
1260 + -90x = 900 + 90x + -90x

Combine like terms: 90x + -90x = 0
1260 + -90x = 900 + 0
1260 + -90x = 900

Add '-1260' to each side of the equation.
1260 + -1260 + -90x = 900 + -1260

Combine like terms: 1260 + -1260 = 0
0 + -90x = 900 + -1260
-90x = 900 + -1260

Combine like terms: 900 + -1260 = -360
-90x = -360

Divide each side by '-90'.
x = 4

Simplifying
x = 4

See similar equations:

| 5/6+30+x | | 0.06(y-6)+0.16y=0.02y-0.5 | | -0.7x+4.86=-0.5x+6.66 | | 13=-d+8 | | -7c+3+5c=-3c+8 | | 2x+12=71 | | (x/58.5)-((1.06-2x)/95)=0.00914 | | 280=10(2x+8) | | -x=-54 | | 3/4y+1/2=7/8y-5/4 | | 2/3+15=21 | | 4w-1=7(w-2) | | 12/36=2w | | 6-3(4x-1)=18-3x | | -9x^2=3 | | 12/6=2w | | 3x-40=5x+20 | | 0.2x-9=2.7x-24 | | 3x^2-18x-36=0 | | 3.2m=-6 | | -7x-17+8x=-8 | | 36x^2-18x-4= | | c(c-4)=9 | | -5(t-4)+7t=6+-7 | | -4x^2-7=0 | | 3/8x=-6 | | x^3-3x^2+6x-6=0 | | -2a+2b+4=0 | | 5y/6+2y/3 | | 3/4+6 | | 1784/76.32=x/12.56 | | 2x+3/3x=7/3-4/x |

Equations solver categories